Regulating abortion in Malaysia / Noor Aqilah Aris, Noor Atiqah Zainal Abidin and Noraiman Amalina Zainordin - Aris, Noor Aqilah; Zainal Abidin, Noor Atiqah; Zainordin, Noraiman Amalina (Faculty of Law, 2012)
This project paper is concern on recommending a law of abortion in Malaysia. Basically in Malaysia, abortion is illegal however there are certain circumstances in which abortion can be carried out. However, most women in Malaysia do not have knowledge on the legality of abortion. As a result, illegal abortion keeps on increasing day by day. The problem become worse when there is no specific act governing abortion in Malaysia other than Section 312 of Penal Code. This project will focus on scrutinizing Section 312 of Penal Code, Indian Penal Code and also Indian Medical Termination of Pregnancy act 1971. A study and research had been conducted in determining the strength and weaknesses of the laws. It also will determine the practicability and effectiveness of these laws. We also include our recommendation and conclusion at the end of our project paper which we hope it would help to make a new law which is more effective regarding to this issue.